Production of Biodiesel from Lipid of Phytoplankton Chaetoceros calcitrans through Ultrasonic Method - Raymond Kwangdinata; Indah Raya; Muhammad Zakir (The Scientific World Journal)
A research on production of biodiesel from lipid of phytoplankton Chaetoceros calcitrans through ultrasonic method has been done. In this research, we carried out a series of phytoplankton cultures to determine the optimum time of growth and biodiesel synthesis process from phytoplankton lipids. Process of biodiesel synthesis consists of two steps, that is, isolation of phytoplankton lipids and biodiesel synthesis from those lipids. Oil isolation process was carried out by ultrasonic extraction method using ethanol 96%, while biodiesel synthesis was carried out by transesterification reaction using methanol and KOH catalyst under sonication. Weight of biodiesel yield per biomass Chaetoceros calcitrans is 35.35%. Characterization of biodiesel was well carried out in terms of physical properties which are density and viscosity and chemical properties which are FFA content, saponification value, and iodine value. These values meet the American Society for Testing and Materials (ASTM D6751) standard levels, except for the viscosity value which was 1.14 g·cm−3.